AN ANALYSIS OF THE WRITTEN GRAMMATICAL ERRORS PRODUCED BY FRESHMENT STUDENTS IN ENGLISH WRITING - Hamzah, Hamzah (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2012)
Abstract This study is aimed at providing explanation on the taxonomy of the grammatical errors made by the university students in written production of English. The data were obtained from twenty English texts written by students as a part of their task in writing class. The findings of the study reveal that the errors can be grouped into fifteen categories ranging from severe errors to mild errors. The categories for severe errors are word choice, verb group, article, preposition, plurality and spelling. The other categories are subject-verb agreement, pronoun agreementa nd dropping, relative clause, possessive, copula omission and mechanic. Based on these findings, the teacher of English are suggested to raise students’ awareness on these errors and provide sufficient remedies to prevent students from internalising such errors. Key words: error correction, error analysis, grammatical error, interlanguage